2021
DOI: 10.1002/ppap.202100104
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nonthermal plasma on the oxidation and removal of particulate matter under different diesel engine loads

Abstract: Nonthermal plasma (NTP) can oxidize and decompose particulate matter (PM) of diesel engines at low temperatures (≤200°C), exhibiting good application prospects. PM samples were collected under different diesel engine loads and were oxidized using an NTP method. The volatile fraction (VF) mass fraction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…After NTP oxidation, the proportion of soot increased from 18–36% to 29–52%. In the experiment of Zhu et al (Zhu et al 2021 ), the SOF after NTP treatment showed different components under different engine loads. At the low and medium loads, there were more low-carbon atoms in the SOF.…”
Section: Diesel Particulate Filter Regenerationmentioning
confidence: 97%
See 1 more Smart Citation
“…After NTP oxidation, the proportion of soot increased from 18–36% to 29–52%. In the experiment of Zhu et al (Zhu et al 2021 ), the SOF after NTP treatment showed different components under different engine loads. At the low and medium loads, there were more low-carbon atoms in the SOF.…”
Section: Diesel Particulate Filter Regenerationmentioning
confidence: 97%
“…Energy is selectively transferred to electrons by the discharge reaction. The free radicals generated by the collision of electrons can oxidize particles at low temperature (Zhu et al 2021 ). The complex chemical reaction of this active substance cannot be realized under normal conditions (Shi et al 2019b ).…”
Section: Diesel Particulate Filter Regenerationmentioning
confidence: 99%
“…As the main components of SOF in the PM, HC combined with O and O 3 to form CO 2 (Equations ( 12) and ( 13)) as shown in Figure 4. Therefore, PM could be efficiency decreased under the NTP treatment due to a reaction with the high oxidative [24,25].…”
Section: Mechanism Of Ntp Technology On Particulate Matter (Pm)mentioning
confidence: 99%
“…11,12 Numerous research results indicated that NTP can effectively purify exhaust pollutants, high-energy electrons and active substances generated by NTP collide with surrounding gas molecules to produce reactive species, the reactive species actively combine with the environmental pollutants to form a decomposition product. 13,14 Meanwhile, NTP can realize the surface modification of catalyst for the purification performance improvement while retaining the inherent properties of catalyst. [15][16][17] The main ways to generate NTP mainly include dielectric barrier discharge (DBD), corona discharge and microwave discharge.…”
Section: Introductionmentioning
confidence: 99%
“…Nonthermal plasma (NTP) is widely considered to be a promising technology by introducing plasma into the exhaust gases 11,12 . Numerous research results indicated that NTP can effectively purify exhaust pollutants, high‐energy electrons and active substances generated by NTP collide with surrounding gas molecules to produce reactive species, the reactive species actively combine with the environmental pollutants to form a decomposition product 13,14 . Meanwhile, NTP can realize the surface modification of catalyst for the purification performance improvement while retaining the inherent properties of catalyst 15–17 .…”
Section: Introductionmentioning
confidence: 99%